Sustainability of wood supply: risk analysis for a pulp mill in Guangxi, China - Varmola, M.; Kanninen, M.; Ning, L.; Daping, X. (IUFRO, 2010)
Finnish-based forest corporation, Stora Enso, is developing and purchasing eucalypt plantations, and establishing a large pulp mill with an approximate production capacity of 1 million tonnes of pulp per year in southern China. The project has been evaluated by recognised international assessment, which concluded that it would be profitable and environmentally and socially sustainable. Wood supply from existing and new plantations was assessed to be sufficient to meet the need of the pulp mill. The conclusions on wood supply were based on very simple estimates and risky assumptions on mean annual increment (MAI) and areas of plantation estate available without fully taking into account many high-risk factors, or at least data are not available in the public domain. This paper discusses several elements that have an effect on sustainability of wood supply, including factors and risks affecting wood production and land availability. The results demonstrate a close relationship between wood production of the plantation itself, and the total area needed to produce a certain amount of wood. At the scale of the case study involved, every 10% change in MAI is equivalent to about 5000 to 40 000 ha of land, depending on growth rates. We show that many new fast-growing eucalypt plantations, in addition to existing ones, are needed for long-term sustainability of wood supply. Moreover, substantial investments in strategic and applied research would be required to achieve high and sustainable production per unit area in the given environment. This means that more actions will be required in the establishment and management of new plantations. The results from the wood supply scenario also reveal the growing importance of corporate responsibility (CR) in the corporate governance agenda of the forest sector. In order to achieve the desired economic, environmental, and social outcomes, national macro-economic planning, a consistent policy and management framework, and a systematic, focused and institutionalised approach to CR are therefore expected from the government and the private sector, respectively